1992
DOI: 10.1099/00207713-42-1-27
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter muridarum sp. nov., a Microaerophilic Helical Bacterium with a Novel Ultrastructure Isolated from the Intestinal Mucosa of Rodents

Abstract: Helical organisms with novel ultrastructural characteristics were isolated from the intestinal mucosa of rats and mice. These bacteria were characterized by the presence of 9 to 11 periplasmic fibers which appeared as concentric helical ridges on the surface of each cell. The cells were motile with a rapid corkscrewlike motion and had bipolar tufts of 10 to 14 sheathed flagella. The bacteria were microaerophilic, nutritionally fastidious, and physiologically similar to Helicobucter species and Wolinella succin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
82
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(83 citation statements)
references
References 10 publications
(12 reference statements)
1
82
0
Order By: Relevance
“…In Salmonella, approximately 11 stator complexes interact with the peptidoglycan layer and 128 P-ring [28,52,53], but C. jejuni has 17 stator complexes positioned at considerably wider diameter. This is 129 also evident in both Helicobacter muridarumand Helicobacter felis, in which freeze-fracture studies revealed 130 approximately 17 'studs' [30,34] previously shown to be stator complexes [54]. Thus in the epsilon-131 proteobacteria imaged so far, additional stator complexes are positioned at a wider radius than in the enteric 132…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…In Salmonella, approximately 11 stator complexes interact with the peptidoglycan layer and 128 P-ring [28,52,53], but C. jejuni has 17 stator complexes positioned at considerably wider diameter. This is 129 also evident in both Helicobacter muridarumand Helicobacter felis, in which freeze-fracture studies revealed 130 approximately 17 'studs' [30,34] previously shown to be stator complexes [54]. Thus in the epsilon-131 proteobacteria imaged so far, additional stator complexes are positioned at a wider radius than in the enteric 132…”
mentioning
confidence: 73%
“…To survive and maintain motility, H. pylori secretes a urease which breaks down urea to 80 form ammonium, raising local pH, and reverting mucous to a viscous fluid. SomeHelicobacter species such 81 as Helicobacter muridarum [34]and Helicobacter trogontum [35] also assemble distinctive helical 82 periplasmic non-flagellar ribs within their periplasm. The significance of these ribs is unclear, but may 83 further augment the spiral characteristics of these species, or reinforce cell shape in bacteria which may be 84 exposed to large torques that might otherwise buckle or mishape the cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…cause clinical disease in rats, causing colitis in naturally and experimentally infected nu/nu rats (Haines et al, 1998;Lee et al, 1992;Mendes et al, 1996). Our finding of natural H. pullorum infection in rats and the ability of H. pullorum to experimentally infect rats warrants further studies to determine whether wild rats are infected with H. pullorum and serve as reservoirs capable of contaminating food stuffs used for poultry or human consumption.…”
Section: Discussionmentioning
confidence: 99%
“…During the past two decades, several Helicobacter species, including H. muridarum (Lee et al 1992), H. hepaticus (Fox et al 1994), H. bilis (Fox et al 1995), H. rodentium (Shen et al 1997), H. typhlonius (Franklin et al 1999(Franklin et al , 2001), H. ganmani (Robertson et al 2001) and Flexispira rappini have been isolated from laboratory mice. F. rappini was named on the basis of its morphology but appears to represent at least 10 Helicobacter taxa, some of which can be found in mice (Dewhirst et al 2000).…”
mentioning
confidence: 99%